Detecção molecular de mycobacterium leprae no tecido do sulco gengival e na saliva em casos de hanseníase - Trize, Débora De Melo (2019)
Leprosy is a chronic infectious disease characterized by changes in tactile, thermal and painful skin sensitivity, due to peripheral nerves involvement. In Brazil is a still endemic disease; fighting it is priority in public health, however, one of the biggest obstacles is the diagnosis. The main route of transmission is done directly, most likely the respiratory tract, requiring a predisposition to acquire the disease. Mycobacterium leprae (M. leprae) is the main causative agent of leprosy and sensitive methods are needed to detect the bactéria. One of the tests of high sensitivity and specificity, the polymerase chain reaction in real time (qPCR) has proved to be a quick, easy and reliable method for molecular detection and quantification of mycobacteria. The aim of this study was to molecularly identify the presence of M. leprae in the tissue of the gingival sulcus and in the saliva, of leprosy, and healthy volunteers. For this, the methodology used was qPCR, in the target gene RLEP (gene repetitive elemento), in DNA samples of M. leprae extracted from the gingival sulcus and saliva. 31 patients with leprosy (GH) and 51 volunteers in the control group (GC) participated in this study. The results were stored in specific and spreadsheets, involving absolute and relative frequencies. It was found that M. leprae was present in saliva and in GH tissue. The qPCR of saliva and positive tissue results from samples with multibacillary characteristics (88.89%), of the borderline lepromatous type (BL) (55.56%), in a reactional state of type 2 (81.5%). The results support the fact that the buccal region may be a site of importance in the early detection and complementary diagnosis of M. leprae.